Development of Orodispersible Ibuprofen Tablets Based on a Polymer-drug Complex - V. R. Timergalieva; R. R. Khusnutdinov; R. R. Musina; E. S. Elizarova; R. R. Alsynbaev; Sh. F. Nasibullin; R. I. Moustafine (Разработка и регистрация лекарственных средств)
Introduction. Orodispersible dosage forms are a very promising direction in the development of dosage forms. Such dosage forms are designed for both systemic and local action of the active pharmaceutical ingredients that make up their composition. Active pharmaceutical ingredients from orodispersible forms enter directly into the systemic circulation, bypassing the "first pass effect".Aim. Development of orodispersible tablets based on the Eudragit® EPO/ibuprofen polymer-drug complex and evaluation of ibuprofen release from the resulting system.Materials and methods. Samples of the polymer-drug complex (PDC) were obtained with different ratios of EPO and ibuprofen, as well as with different mixing orders. Turbidimetric studies to find the stoichiometry of the resulting EPO/IB PLC were performed spectrophotometrically (Lambda 25, PerkinElmer, U.S.A.) at a wavelength of 600 nm. Thermal analysis was performed by modulation differential scanning calorimetry (mDSC) on a Discovery™ DSC instrument (TA Instruments, U.S.A.). Samples sealed in Tzero aluminum pans (TA Instruments, U.S.A.) were scanned in the temperature range from 0 to 250 °С at a speed of 2 °С/min. IR spectra were recorded on a Nicolet iS5 FT-IR spectrometer (Thermo Fisher Scientific, U.S.A.) with an ATR nozzle, in the range from 500 to 4000 cm-1. Drying of samples of complexes and dispersible tablets was carried out in a FreeZone 1L laboratory freeze dryer (Labconco, U.S.A.) for a 24 hours at a temperature of –49 °C and at a pressure of 0.350 mbar. The drug release was evaluated on a dissolution tester DT 828 (ERWEKA GmbH, Germany) in a volume of 900 ml, at 37 ± 0.5 °C and a blade rotation speed of 50 rpm.Results and discussion. Studies on the formation of PDC Eudragit® EPO/ibuprofen (EPO/IB) were carried out at various molar ratios. On samples of PDC and individual components, bands are observed that are characteristic both for EPO – at 2770 and 2820 cm-1, confirming the presence of non-ionized dimethylamino groups, and at 1725 cm-1, corresponding to the stretching vibrations of carboxyl groups. A new band is appeared at 1573 cm-1, which confirm the formation of ionic bonds between carboxylate groups of IB and ionized dimethylamino groups of EPO. The mDSC thermograms of the samples are characterized by a single glass transition temperature (Tg) at 27,3 ± 0,3 °С (for molar ratio 1 : 2) and 44,9 ± 0,4 °С. (for molar ratio 1 : 1), which confirm the formation of polymer-drug complexes. Received PDC Eudragit® EPO/ibuprofen in a molar ratio of 1 : 2 and 1 : 1 and oral dispersible tablets based on them by lyophilization. The resulting systems are characterized by immediate release of IB with maximum rates at 30 min for a 1 : 1 composition and 60 min for a 1 : 2 composition.Conclusion. Eudragit® EPO/ibuprofen polymer drug complex can be used to develop orodispersible tablets providing immediate release of IB.